Diversity of Portanini (Insecta: Hemiptera: Cicadellidae) from Parque Nacional do Itatiaia, Southeastern Brazil, with descriptions of two new species - Anselmini, Luiza Silva; Prando, Jádila Santos; Takiya, Daniela Maeda (Zootaxa, 2022)
A survey of Portanini (Insecta: Hemiptera: Cicadellidae) from Parque Nacional do Itatiaia, Southeastern Brazil was conducted. This survey resulted in an increase of the known diversity of Portanini from one to four species in the area. Portanus youngi Linnavuori, 1959 is newly recorded from Minas Gerais State and Itatiaia and Resende municipalities (Rio de Janeiro State), while Portanus felixi Carvalho, 2012 is newly recorded from the municipality of Itatiaia (Rio de Janeiro State). In addition, two new species of Portanini are described: Portanus cornutus sp. nov. and Portanus spherae sp. nov. from Rio de Janeiro State. The former can be distinguished from other Portanus species by four short longitudinal white stripes on posterior margin of crown and pygofer lobe long and with ventrally curved processes. The latter can be distinguished from other Portanus species by a pair of long posteroventral spiniform processes on pygofer; aedeagus with long preatrium, robust atrium, long dorsal apodemes, and shaft directed dorsally; and internal female sternite VIII sclerotized.